Do Fiscal Councils Affect the Management of National Public Finances? A Quasi-experimental Study with Panel Data - Marcano, Jesús; Sánchez, Karla; Puente, José Manuel (Universidad de los Andes, Colombia, 2024)
The public deficit and debt levels of Western countries have increased significantly over the past 30 years. In response,the implementation of fiscal councils has become increasingly popular as a means to mitigate deficit bias. These institutions seek to deter deficit-oriented resource management by providing information on the state of public finances,thereby enhancing cit-izen oversight and promoting responsible government administration. This study evaluates the effectiveness of these institutions using an identification strategy based on synthetic control and difference-in-differences techniques. Although some of the resulting estimates suggest favorable impacts on the primary balance,the majority indicate that fiscal councils do not significantly influence fiscal management. Con-sequently,no conclusive evidence has been found on the effectiveness of these institutions. © 2024,Universidad de los Andes,Colombia. All rights reserved.
[¿Los consejos fiscales inciden en la gestión de las finanzas públicas nacionales? Un estudio cuasiexperimental con datos de panel]
Keywords: 53 Ciencias Económicas; ODS 17 - Alianzas para lograr los objetivos